2013
DOI: 10.1063/1.4794019
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and observation of variable range hopping conduction mechanism at high temperature in CdSe quantum dot solids

Abstract: Articles you may be interested inEffect of metal oxide morphology on electron injection from CdSe quantum dots to ZnO A mirage study of CdSe colloidal quantum dot films, Urbach tail, and surface states J. Chem. Phys. 137, 154704 (2012); 10.1063/1.4758318 Preparation, characterization and luminescence properties of polyaniline-CdS nanocomposites AIP Conf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Where J max is given by the relation [42] , it has been observed that the J max values are lower than the values of J over the investigated temperature range 298 K to 523 K. Therefore we may conclude that the adiabatic small polaron model is suitable to describe the thermal behavior of conductivity. Similar behavior has been obtained in CdSe quantum dot [38]. At lower temperature, a deviation from linearity has been observed due to weak polaronic hopping conduction.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Where J max is given by the relation [42] , it has been observed that the J max values are lower than the values of J over the investigated temperature range 298 K to 523 K. Therefore we may conclude that the adiabatic small polaron model is suitable to describe the thermal behavior of conductivity. Similar behavior has been obtained in CdSe quantum dot [38]. At lower temperature, a deviation from linearity has been observed due to weak polaronic hopping conduction.…”
Section: Resultssupporting
confidence: 69%
“…For electrical measurement, first pellets having 1 cm diameter were made by pressing the powder at 500 MPa hydraulic pressures and fine copper wire was attached to it by highly conducting silver paste. The details experimental technique was described in the previous publications [38,39].…”
Section: Methodsmentioning
confidence: 99%
“…Due to large surface to volume ratio and quantum confinement effects, the nanomaterials exhibit novel electrical, magnetic and optical properties as compared to their bulk counterparts. Recently, nanostructures viz., nanoparticles, nanofibers, nanotubes, QD etc have received remarkable attention among the scientific community owing to their potential applications [20][21][22][23][24]. Despite the remarkable progress in the field of nanostructures, both in terms of fundamental and technological viewpoints, charge transport mechanism in such disordered low dimensional structures has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…We have followed here a modified low temperature synthesis procedure [17]. Sodium selenosulfate (Na 2 SeSO 3 ) was prepared by a method described previously [4]. It was then kept as a source of selenium (Se 2À ) ions.…”
Section: Methodsmentioning
confidence: 99%